Exploring University-Based Teacher Educators’ Identities through the Prism of Curriculum Planning - Chamo, Nurit; Biberman-Shalev, Liat; Ram, Drorit (Journal of Ecohumanism, 2024)
The professional identity of university-based teacher educators (UBTEs) is a multifaceted construct, with the curricular domain serving as a central component. This study aims to investigate the nature of the curricular field within the professional identity of twelve UBTEs (N=12). Drawing upon a phenomenological qualitative approach, data were gathered through semi-structured interviews and self-reflection documents. Thematic content analysis was employed to discern patterns and themes in UBTEs’ perceptions of curriculum planning processes and of the curriculum of pedagogical supervision. Results revealed diverse perspectives, ranging from broad conceptualizations of curriculum planning to nuanced discussions on variations in curriculum design and adaptation in response to diverse needs of preservice teachers and UBTEs’ interpretations. This study not only contributes to the ongoing discourse on UBTEs’ professional identity, but also provides insights into curriculum development processes, particularly in the context of educational transitions such as those precipitated by the COVID-19 pandemic.